Building a buzz libraries & word-of-mouth marketing - Barber, Peggy (IG library, 2010)
Want to get the word out about your library in the most cost-effective way possible? You can achieve this with the effective word-of-mouth marketing (WOMM) strategies laid out in this book. Two creative marketers, Peggy Barber and Linda Wallace, bring you sound marketing principles to spread the word about your library within the community with: a strategy that works for you, WOMM must-haves, tips to effectively deliver your message, and best practices and insightful reviews. Renown for their creativity, Barber and Wallace bring you WOMM ideas that will help you turn your existing library patrons into a major marketing force.